2017
DOI: 10.5465/annals.2014.0066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dual Nature of Ambivalence: Why and When Ambivalence Leads to Good and Bad Outcomes

Abstract: A growing body of research unveils the ubiquity of ambivalence-the simultaneous experience of positive and negative emotional or cognitive orientations towards a person, situation, object, task, or goal-in organizations, and argues that its experience may be the norm rather than the exception. While traditionally viewed as something to be avoided, organizational scholars in fields ranging from micro-organizational behavior to strategy have made significant advances in exploring the positive outcomes of ambival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
255
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(271 citation statements)
references
References 176 publications
16
255
0
Order By: Relevance
“…As a result, while the overall relationship between conflict and compatibility demonstrated a strong inverse correlation (as described above in the Methods section), we did see instances of coactivation that showed evidence of both conflict and compatibility (see Table ). These reports align with the notion of ambivalence, or the experience of simultaneous positive and negative orientations toward a situation (Rothman et al, ). We see ambivalence in identity coactivation as a fruitful area for future research because it addresses situations where both conflict and compatibility are experienced.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…As a result, while the overall relationship between conflict and compatibility demonstrated a strong inverse correlation (as described above in the Methods section), we did see instances of coactivation that showed evidence of both conflict and compatibility (see Table ). These reports align with the notion of ambivalence, or the experience of simultaneous positive and negative orientations toward a situation (Rothman et al, ). We see ambivalence in identity coactivation as a fruitful area for future research because it addresses situations where both conflict and compatibility are experienced.…”
Section: Discussionsupporting
confidence: 73%
“…We see ambivalence in identity coactivation as a fruitful area for future research because it addresses situations where both conflict and compatibility are experienced. Rothman and colleagues () have suggested that ambivalence may produce flexibility or inflexibility as well as engagement or disengagement with the circumstances producing ambivalence. Future research should consider these outcomes as potential responses to the coactivation experience in addition to the emotional response found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, appetitive and aversive processing operate within the same brain regions and involve similar neurotransmitter systems (Hayes, Duncan, Xu, & Northoff, 2014;Hu, 2016;Pessiglione & Delgado, 2015). Other research also highlights the prevalence of affective, attitudinal, and motivational ambivalence (Larsen, Hershfield, Stastny, & Hester, 2017;Mikulincer, Shaver, Bar-On, & Ein-Dor, 2010;Rothman, Pratt, Rees, & Vogus, 2016). In research on goals, in particular, substantial positive correlations between approach and avoidance variants are observed (Gable, 2006;Mouratidis & Sideridis, 2009;Ryan & Shim, 2008).…”
Section: Lay Conceptions About Norm-based Approach and Avoidance Momentioning
confidence: 99%
“…We argue that individuals are capable of consciously dealing with the conflicting demands of exploitation and exploration when situations are found to be adversarial or ambivalent (Lewis, 2000;Lüscher and Lewis, 2008;Putnam et al, 2016;Rothman et al, 2017). This relates to the general notion that conflicts must first be detected and recognized 28 by people, before they can be managed (Rahim, 2002: 207).…”
Section: Conflicts Within the Contextual Approach: Enabling Individualsmentioning
confidence: 99%